2018
DOI: 10.1111/mec.14902
|View full text |Cite
|
Sign up to set email alerts
|

Deciphering the drivers of negative species–genetic diversity correlation in Alpine amphibians

Abstract: The evolutionary and ecological importance of neutral and adaptive genetic diversity is widely recognized. Nevertheless, genetic diversity is rarely assessed for conservation planning, which often implicitly assumes a positive correlation between species and genetic diversity. Multiple drivers can cause the co‐variation between the genetic diversity of one species and the richness of the whole communities, and explicit tests are needed to identify the processes that can determine species–genetic diversity corr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 95 publications
(161 reference statements)
1
19
0
Order By: Relevance
“…Our results contribute to the idea that disentangling intraspecific diversity patterns can be much more complicated than species richness as many factors require simultaneous consideration (see Blanchet et al, 2017;Marchesini et al, 2018;Martinez et al, 2018;Medina et al, 2018;Millette et al, 2019;Paz-Vinas et al, 2018;Willoughby et al, 2017). The limited scope in the scale of genetic diversity, and perhaps the minimum and maximum degree of genetic diversity required for viable populations (e.g.…”
Section: Ne W Analys Is Summarymentioning
confidence: 64%
See 3 more Smart Citations
“…Our results contribute to the idea that disentangling intraspecific diversity patterns can be much more complicated than species richness as many factors require simultaneous consideration (see Blanchet et al, 2017;Marchesini et al, 2018;Martinez et al, 2018;Medina et al, 2018;Millette et al, 2019;Paz-Vinas et al, 2018;Willoughby et al, 2017). The limited scope in the scale of genetic diversity, and perhaps the minimum and maximum degree of genetic diversity required for viable populations (e.g.…”
Section: Ne W Analys Is Summarymentioning
confidence: 64%
“…Large quantities of data on intraspecific diversity have recently become available for broad-scale analyses due to technological advances and the accumulation of smaller-scale empirical works (DeWoody & Avise, 2000;Hughes, Daily, & Ehrlich, 1997;Lawrence et al, 2019;Martinez, Willoughby, & Christie, 2018;Medina, Cooke, & Ord, 2018;Miraldo et al, 2016;Willoughby et al, 2015). When collated, such data allow for the extension of species-centric latitudinal concepts towards understanding how broad-scale intraspecific diversity patterns may better inform, for example, the speciation process (Adams & Hadly, 2013;Schluter & Pennell, 2017;Smith, Seeholzer, Harvey, Cuervo, & Brumfield, 2017) and biodiversity conservation by revealing hot/cold spots of intraspecific diversity (Marchesini, Vernesi, Battisti, & Ficetola, 2018;Paz-Vinas et al, 2018). Herein, we focus our discussion specifically on broad-scale patterns of two metrics of intraspecific diversity: population richness within species and genetic diversity, and how these metrics relate to species richness gradients.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Secondly, it is a matter of fact that for the flora of the Alps and other large mountain ranges, species richness only partly correlates to genetic diversity. In a milestone contribution to this subject, [ 8 ] demonstrated that while the highest species richness is found in the South-Western Alps, the greatest genetic diversity within and among species is located in the central and eastern part of the Alpine chain [ 9 , 10 , 11 , 12 ]. Environmental characteristics can influence taxonomic and genetic diversity in different ways, resulting in a negative correlation between these two features [ 13 ].…”
Section: Introductionmentioning
confidence: 99%